Analysis of the flow profile of six endodontic cements - Denise Piotto Leonardi; Antonio Batista; Marili Doro Andrade Deonizio; Gilson Blitzkow Sydney; Mônica Ferreira (Faculdade São Leopoldo Mandic, 2009)
Objective: To assess the flow characteristic of six endodontic filling cements by means of the vertical flow test: N-Rickert (Fórmula e Ação, São Paulo, Brazil), Endofill (Dentsply, Petrópolis, Brazil), Zinc Oxide and Eugenol (SS White, Rio de Janeiro, Brazil), AH-Plus (Dentsply, Petrópolis, Brazil), EndoRez (Ultradent, South Jordan, UT, USA) and Intra-Fill (SS White, Rio de Janeiro, Brazil).Methods: Flow test was performed by placing the 0.1 ml samples of cements between two plates of polished glass measuring 30 x 26 cm. Thesamples were deposited on the top part with aid of a insulin syringe. The plates were taken to an oven at 37o and relative humidity of 100%.Flow was measured by means of a sheet of millimetric paper placed between the glass plates, at time intervals of 10 minutes, 20 minutes, 30 minutes, one hour, two hours, three hours, four hours, five hours, six hours, 12 hours, 24 hours and 48 hours.Results: Endofill (Dentsply, Petrópolis, Brazil) showed flow of 69.3mm, followed by N-Rickert (Fórmula e Ação, São Paulo, Brazil) (43.0mm) and AH-Plus (Dentsply, Petrópolis, Brazil) (29.3mm). The cements Intrafill (SS White, Rio de Janeiro, Brazil), Zinc Oxide and Eugenol (SS White, Rio de Janeiro, Brazil) and EndoRez (Ultradent, South Jordan, UT, USA) presented no flow. N-Rickert (Fórmula e Ação, São Paulo, Brazil) and Endofill (Dentsply, Petrópolis, Brazil) behaved similarly, and needed no initial force to become displaced. The cement N-Rickert (Fórmula e Ação, São Paulo, Brazil) flowed for up to thirty minutes and Endofill (Dentsply, Petrópolis, Brazil) up to the second hour of observation. Initial flow of AH-Plus (Dentsply, Petrópolis, Brazil) was 0.8mm up to three hours, remaining stable after the fifth hour. Conclusion: The cements Zinc Oxide and Eugenol (SS White, Rio de Janeiro, Brazil), Intrafill (SS White, Rio de Janeiro, Brazil) and EndoRez (Ultradent, South Jordan, UT, USA) did not present any flow during the experiment. The greatest flow was for Endofill (Dentsply, Petrópolis, Brazil) followed by N-Rickert (Fórmula e Ação, São Paulo, Brazil) and AH-Plus (Dentsply, Petrópolis, Brazil) with a significant statistical difference(p<0.01).